Proposed Inclusive Business Ecosystem of Gedong Gincu. Case study: Cirebon, Indramayu, Majalengka, Kuningan, and Sumedang District - Erlisafitri, Erlisafitri; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2015)
Abstract. Indonesia occupied the 6th position (2011) as the largest mango producer in the world, where almost all provinces in Indonesia are able to produce different varieties of mango. GedongGincu as "The Queen of Mango" became one of the flagship varieties of mango after Arummanis which is West Java as producer. High demand of GedongGincu in export market is faced with declining of production, both in terms of quality and quantity. Problem analysis was done through focus group discussion (FGD) and semi-structured interviews to business stakeholders in five production centers such as the Department of Agriculture, Department of Industry and Trade, and BAPPEDA (provincial and district), Coordination Instructor Agency, farmers, exporter, supermarket, collector, trader/ retailer, processors, cooperative, input provider, and universities. Declining of production occurs due to lack of collaboration among business stakeholder which this depicted through the relationship condition that is still transactional or enhancement based on collaboration value exchange. This relationship condition caused problems such as market information, ineffective regulatory environments, inadequateinfrastructure, lack of knowledge and skills, and limited access to capital. Market competition and the increasing demand of buyers demanded economic conditions which stimulate business players to be more aggressive in winning business competition. For that, this business need collaborative network among business stakeholder which integrates stakeholders from upstream to downstream. Network Collaboration required linkages between business stakeholders such as collaborative value exchange between customers and manufacturers, collaborative business process between manufacturers with partners and suppliers and collaborative business networks among key resources and partnerships.Keywords: GedongGincu, Collaboration Value Exchange (CVE)